On the performance of non-coherent transmission schemes with equal-gain combining in generalized Κ-fading - Zhu, Cindy; Mietzner, Jan; Schober, Robert (IEEE Transactions on Wireless Communications, 2010)
The generalized Κ-fading model, characterized by two parameters, κ and m, is a very versatile model and was recently shown to accurately capture the effects of composite shadowing and multipath fading in wireless communication systems. Furthermore, it can be used to model cascade multipath fading, which is relevant in, e.g., mobile-to-mobile communication scenarios. In this paper, we derive closed-form expressions for the bit error probability of two non-coherent transmission schemes over L diversity branches being subject to generalized Κfading. Specifically, focus is on binary differential phase-shift keying (DPSK) and binary non-coherent frequency-shift keying (FSK) modulation with (post-detection) equal-gain combining at the receiver. We also discuss the extension of our results to M-ary modulation schemes. Considering both independent and correlated fading across the L branches, we derive expressions for the asymptotic diversity order, which reveal an interesting interplay between the two fading parameters κ and m. Moreover, we show that the diversity order of the considered non-coherent transmission schemes is the same as in the case of a coherent transmission scheme. Finally, numerical performance results are presented, and our analytical results are corroborated by means of Monte-Carlo simulations. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Κ-fading; Cascade fading; Diversity reception; Fading channels; Non-coherent transmission; Performance analysis; Shadowing